2021
DOI: 10.1101/2021.10.25.465362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cytoskeletal Vortex Drives Phage Nucleus Rotation During Jumbo Phage Replication in E. coli

Abstract: Vortex-like arrays of cytoskeletal filaments that drive cytoplasmic streaming and nucleus rotation have been identified in eukaryotes, but similar structures have not been described in prokaryotes. The only known example of a rotating intracellular body in prokaryotic cells occurs when nucleus-forming jumbo phages infect Pseudomonas. During infection, a bipolar spindle of PhuZ filaments drives intracellular rotation of the phage nucleus, a key aspect of the replication cycle. Here we show the E. coli jumbo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Therefore, it seems likely that these assemblages are not essential for these phages to reproduce. However, we have recently shown that Escherichia coli jumbo phage Goslar also forms a nucleus and large phage bouquets late during infection, demonstrating that this phenomenon is conserved in a distantly related jumbo phage (41). We do not observe intact bouquets after cell lysis by fluorescence microscopy, suggesting that they do not survive the forceful lysis of the host cell.…”
Section: Resultsmentioning
confidence: 53%
“…Therefore, it seems likely that these assemblages are not essential for these phages to reproduce. However, we have recently shown that Escherichia coli jumbo phage Goslar also forms a nucleus and large phage bouquets late during infection, demonstrating that this phenomenon is conserved in a distantly related jumbo phage (41). We do not observe intact bouquets after cell lysis by fluorescence microscopy, suggesting that they do not survive the forceful lysis of the host cell.…”
Section: Resultsmentioning
confidence: 53%
“…We recently discovered that the E. coli bacteriophage Goslar assembles a nuclear shell morphologically similar to those observed in the Pseudomonas phage 201φ2-1, φPA3, and φKZ (16). Goslar encodes a divergent homolog of 201φ2-1 chimallin (gp189), with 19.3% overall sequence identity between the two proteins ( Fig.…”
Section: Resultsmentioning
confidence: 76%
“…The E. coli jumbo bacteriophage Goslar (237 kb genome) assembles a nuclear shell morphologically similar to those observed in the Pseudomonas phages 201phi2-1, PhiPA3 and PhiKZ 15 . Goslar encodes a divergent homologue of 201phi2-1 chimallin (gp189, 631 amino acids), with 19.3% overall sequence identity between the two proteins (Fig.…”
Section: Nuclear Shell Architecture Is Conservedmentioning
confidence: 64%